O estudo da acústica a partir de unidades de ensino potencialmente significativas: contribuições para uma aprendizagem significativa - Decian, Emanoela (2020)
This investigation presents the results obtained from the elaborating and implementing of a Potentially Meaningful Teaching Unit (PMTU) on the concepts of Acoustics. The following research is based on David Ausubel’s Meaningful Learning Theory and Marco Antônio Moreira’s Critic Meaningful Learning Theory theoretical references, and attempted to answer to the following question: in what way does the implementing of PMTU favors the meaningful learning of Acoustics’ concepts by sophomore students from a public High School in Santa Maria/RS? In order to do so, we used, as instruments of data collection, surveys for the identification of students’ previous knowledges by sophomore students from a public High School about the concepts related to sound, introductory-level surveys about the same concepts, building of musical devices, mind and conceptual maps, as well as the individual summative evaluation done in the end of the PMTU’s activities, which were implemented in October and November, 2019. The analysis of the instruments was done in a qualitative approach and demonstrated that students presented significative conceptual evolution about sound waves’ content during the activities. Therefore, it is possible to confirm that the utilization of PMTU eased students’ meaningful learning, as it allowed them to improve/change their initial understandings, besides showing itself as an important pedagogic strategy, which can be an incentive for its more frequent use.